How do recorded mental health recovery narratives create connection and improve hopefulness?. (4th March 2022) - Ng, Fiona; Newby, Christopher; Robinson, Clare; Llewellyn-Beardsley, Joy; Yeo, Caroline; Roe, James; Rennick-Egglestone, Stefan; Smith, Roger; Booth, Susie; Bailey, Sylvia; Castelein, Stynke; Callard, Felicity; et al.
Abstract: Background: Mental health recovery narratives are an active ingredient of recovery-oriented interventions such as peer support. Recovery narratives can create connection and hope, but there is limited evidence on the predictors of impact. Aims: The aim of this study was to identify characteristics of the narrator, narrative content and participant which predict the short-term impact of recovery narratives on participants. Method: Independent studies were conducted in an experimental ( n  = 40) and a clinical setting ( n  = 13). In both studies, participants with mental health problems received recorded recovery narratives and rated impact on hopefulness and connection. Predictive characteristics were identified using multi-level modelling. Results: The experimental study found that narratives portraying a narrator as living well with mental health problems that is intermediate between no and full recovery, generated higher self-rated levels of hopefulness. Participants from ethnic minority backgrounds had lower levels of connection with narrators compared to participants from a white background, potentially due to reduced visibility of a narrator's diversity characteristics. Conclusions: Narratives describing partial but not complete recovery and matching on ethnicity may lead to a higher impact. Having access to narratives portraying a range of narrator characteristics to maximise the possibility of a beneficial impact on connection and hopefulness.